2020
DOI: 10.21776/ub.biotropika.2020.008.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Pertumbuhan Jenis Invasif Acacia decurrens Willd. dan Pengaruh Naungannya Terhadap Tanaman Restorasi

Abstract: TNGM melakukan restorasi pasca letusan dengan membuat demonstrasi plot (demplot) restorasi menggunakan jenis tanaman puspa (Schima wallichii), salam (Syzygium polyanthum), dan gayam (Inocarpus edulis) sebagai tanaman inti restorasi. Di saat yang sama, jenis asing Acacia deccurens yang muncul sejak erupsi tahun 2006 mendominasi dan merubah struktur serta komposisi jenis yang ada di kawasan pasca erupsi tahun 2010. Keberadaan A. decurrens yang melimpah dalam demplot diperkirakan mengganggu pertumbuhan tanaman in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Tanaman eksotik ini mempunyai karakteristik khusus yang membuatnya mampu berkembang biak secara cepat dan agresif dan berkompetisi dengan flora dan fauna lain membentuk populasi yang padat dan memengaruhi berkembangan komunitas biotik. A. decurens dilaporkan muncul dan mendominasi tumbuhan di Kawasan Taman nasional Gunung Merapi setelah kebakaran kawasan (Ramadhan et al, 2020;Suryawan, 2015).…”
Section: Hasil Dan Pembahasanunclassified
“…Tanaman eksotik ini mempunyai karakteristik khusus yang membuatnya mampu berkembang biak secara cepat dan agresif dan berkompetisi dengan flora dan fauna lain membentuk populasi yang padat dan memengaruhi berkembangan komunitas biotik. A. decurens dilaporkan muncul dan mendominasi tumbuhan di Kawasan Taman nasional Gunung Merapi setelah kebakaran kawasan (Ramadhan et al, 2020;Suryawan, 2015).…”
Section: Hasil Dan Pembahasanunclassified
“…Then ecological factors are considered by identifying plant species that threaten the environment (invasive series). Invasive plant species can endanger native plant species and harm ecosystems (Sutomo 2018;Ramadhan et al 2020).…”
Section: Ecological Suitabilitymentioning
confidence: 99%
“…Meanwhile, Beechwood (G. arborea ), has a natural range that stretches from South Asia to Southeast Asia, including Indonesia. Invasive plant species have a harmful influence on humans in addition to the environment, notably in the areas of human health and the economy (Sutomo 2018;Ramadhan et al 2020). Characteristics of invasive plant species can lead to the extinction of native species.…”
Section: Ecological Suitabilitymentioning
confidence: 99%
“…The gum (21.03 grams) was extracted sequentially with n-hexane, ethanol, and water as solvents. The extraction duration was six hours for each solvent using the reflux technique at the boiling point temperature of each solvent, namely 68°C, 78.3°C, and 100°C for n-hexane (Ramadhan et al 2020), ethanol, and water, respectively (American Chemical Society 2019).…”
Section: Extraction Of a Decurrens Gummentioning
confidence: 99%
“…In this research, the tree diameter class used for gum tapping was >10 cm. Based on previous studies and field observations, this diameter class was dominant in the populations (Ramadhan et al 2020), and therefore, it could meet the data collection requirements. The preliminary study suggested that the yields of gum tapping of A. decurrens trees varied ranged between 0.05 and 7.84 grams/tree/harvesting.…”
Section: Yield Of a Decurrens Gum Extractmentioning
confidence: 99%